2010
DOI: 10.5194/angeo-28-1317-2010
|View full text |Cite
|
Sign up to set email alerts
|

Beam-excited whistler waves at oblique propagation with relation to STEREO radiation belt observations

Abstract: Abstract. Isotropic electron beams are considered to explain the excitation of whistler waves which have been observed by the STEREO satellite in the Earth's radiation belt. Aside from their large amplitudes (∼240 mV/m), another main signature is the strongly inclined propagation direction relative to the ambient magnetic field. Electron temperature anisotropy with T e⊥ > T e , which preferentially generates parallel propagating whistler waves, can be excluded as a free energy source. The instability arises du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 11 publications
3
52
1
Order By: Relevance
“…Subsequent kinetic simulations by Sydora et al (2007) have shown that during the nonlinear saturation of the temperature anisotropy instability a significant wave number shift (from large k values) to the Gendrin point (where phase and group velocity coincide) takes place accompanied by the formation of whistler oscillitons. As discussed in a recent paper by Sauer and Sydora (2010), a similar process happens during beam excitation of obliquely propagating whistler modes. The importance of whistler Gendrin modes has also been pointed out recently by Verkhoglyadova and Tsurutani (2009) showing that the measured propagation direction of a chorus event in the Earth's magnetosphere agrees well with the calculated Gendrin angle.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Subsequent kinetic simulations by Sydora et al (2007) have shown that during the nonlinear saturation of the temperature anisotropy instability a significant wave number shift (from large k values) to the Gendrin point (where phase and group velocity coincide) takes place accompanied by the formation of whistler oscillitons. As discussed in a recent paper by Sauer and Sydora (2010), a similar process happens during beam excitation of obliquely propagating whistler modes. The importance of whistler Gendrin modes has also been pointed out recently by Verkhoglyadova and Tsurutani (2009) showing that the measured propagation direction of a chorus event in the Earth's magnetosphere agrees well with the calculated Gendrin angle.…”
Section: Introductionmentioning
confidence: 93%
“…4 to study this mechanism of instability. As suggested by other whistler wave studies (Sydora et al, 2007;Sauer and Sydora, 2010), results of particle-in cell (PIC) simulations are presented in Sect. 5 which show that WL oscillitons are formed in the quasi-stationary saturated state of the beam-plasma interaction.…”
Section: K Sauer and R D Sydora: Whistler-langmuir Oscillitons Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Hwang et al (2014a), using both Cluster observations and linear theory, further explored wave enhancements behind DFs and found that two wave modes: a high-frequency beam mode and a low-frequency whistler mode, are associated with a localized electron beam. The generation of whistlers is associated with the electron beam components that can persist for a significant time before being quickly thermalized (Sauer and Sydora 2010). Considering the earthward motion of the DF flux tube, Fermi acceleration related to a shortening of the magnetic field lines contributes to preventing such electron beams from being rapidly thermalized, which can generate whistlers that can in turn energize particles, possibly leading to ion bulk heating.…”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 99%